Total Quality Management (TQM) And Its Implementation In Islamic Education Management - Ikhsan, Nanda Fadila; Salim, Cicik Rohmaniyah; Tasya, Dinar Ayu (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This article discusses the concept of Total Quality Management (TQM) and its application in the context of education, specifically Islamic education. TQM is an approach that encompasses two interconnected concepts: the philosophy of continuous improvement and methods such as brainstorming and field analysis to enhance quality. The article explains that TQM is a holistic and systematic approach aimed at achieving long-term excellence in quality, with a focus on customers and a commitment to continuous improvement. The concept of Total Quality Management (TQM) in education addresses aspects such as customer service, participation of all relevant parties, measurement of graduate quality, stakeholder commitment, and continuous improvement. The success of TQM is measured through customer satisfaction levels, both among students and parents. Awareness of individual responsibility and collaboration within the educational community are crucial for the implementation of TQM. In addressing the challenges of Islamic education, this article proposes the application of the TQM approach, which includes important aspects such as customer focus, participation of all relevant parties, evidence-based approach, leadership commitment, and systemic approach. The article provides an in-depth analysis that by applying TQM principles, educational institutions can create an environment focused on continuous improvement, resulting in better educational quality and the development of outstanding human resources. Keywords: Quality Management, Islamic Education, Educational Management